Evolution of spin excitations into the superconducting state in FeTe1-xSex - Lumsden, M D; Christianson, A D; Goremychkin, E A; Nagler, S E; Mook, H A; Stone, M B; Abernathy, D L; Guidi, T; MacDougall, G J; de la Cruz, C; Sefat, A S; McGuire, M A; et al. (arXiv.org, 2009)
The nature of the superconducting state in the recently discovered Fe-based superconductors1-3 is the subject of intense scrutiny. Neutron scattering investigations have already elucidated a strong correlation between magnetism and superconductivity in the form of a spin resonance in the magnetic excitation spectrum4-7. A central unanswered question concerns the nature of the normal state spin fluctuations which may be responsible for the pairing mechanism. Here we show inelastic neutron scattering measurements of Fe1.04Te0.73Se0.27, not superconducting in bulk, and FeTe0.51Se0.49, a bulk superconductor. These measurements demonstrate that the spin fluctuation spectrum is dominated by two-dimensional incommensurate excitations near the (1/2,1/2) (square lattice (pi,0)) wavevector, the wavevector of interest in other Fe-based superconductors, that extend to energies at least as high as 300 meV. Most importantly, the spin excitations in Fe1+yTe1-xSex exhibit four-fold symmetry about the (1,0) (square lattice (pi,pi)) wavevector and are described by the identical wavevector as the normal state spin excitations in the high-TC cuprates8-12 demonstrating a commonality between the magnetism in these classes of materials which perhaps extends to a common origin for superconductivity.